2019
DOI: 10.1108/el-02-2019-0044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring repost features of police-generated microblogs through topic and sentiment analysis

Abstract: Purpose This study aims to explore the repost features of microblogs acting to promote the information diffusion of government-generated content on social media. Design/methodology/approach This study proposes a topic−sentiment analysis using a mixed social media analytics framework to analyse the microblogs collected from the Sina Weibo accounts of 30 Chinese provincial police departments. On the basis of this analysis, this study presents the distribution of reposted microblogs and reveals the reposting ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Secondly, scholars have extensively studied the influences of content type (Bhattacharya et al, 2017;Bons� on et al, 2015Bons� on et al, , 2019; Bons� on & Bedn� arov� a, 2018; Lee & Xu, 2018;Rahim et al, 2019;Tang et al, 2019), multimedia feature (Bhattacharya et al, 2017;Bons� on et al, 2015Bons� on et al, , 2019Lee & Xu, 2018;Rahim et al, 2019), emotions (Bhattacharya et al, 2017;Haro-de-Rosario, S� aez-Martín, & delCarmen Caba-P� erez, 2018;Tang et al, 2019;Zavattaro et al, 2015), del Mar G� alvez-Rodríguez et al, 2018;Haro-de-Rosario et al, 2018) on CEGSM. Only one study by del Mar G� alvez-Rodríguez et al (2018) employed the DCT to investigate citizen engagement through the Facebook accounts of local Latin American governments; their results confirmed that the generation of new visits, dialogic loop and information of interest to stakeholders, which belongs to the principles of DCT, promotes citizen engagement (the weighted statistics of likes, shares, comments and posts).…”
Section: Citizen Engagement Through Government Social Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, scholars have extensively studied the influences of content type (Bhattacharya et al, 2017;Bons� on et al, 2015Bons� on et al, , 2019; Bons� on & Bedn� arov� a, 2018; Lee & Xu, 2018;Rahim et al, 2019;Tang et al, 2019), multimedia feature (Bhattacharya et al, 2017;Bons� on et al, 2015Bons� on et al, , 2019Lee & Xu, 2018;Rahim et al, 2019), emotions (Bhattacharya et al, 2017;Haro-de-Rosario, S� aez-Martín, & delCarmen Caba-P� erez, 2018;Tang et al, 2019;Zavattaro et al, 2015), del Mar G� alvez-Rodríguez et al, 2018;Haro-de-Rosario et al, 2018) on CEGSM. Only one study by del Mar G� alvez-Rodríguez et al (2018) employed the DCT to investigate citizen engagement through the Facebook accounts of local Latin American governments; their results confirmed that the generation of new visits, dialogic loop and information of interest to stakeholders, which belongs to the principles of DCT, promotes citizen engagement (the weighted statistics of likes, shares, comments and posts).…”
Section: Citizen Engagement Through Government Social Mediamentioning
confidence: 99%
“…Zavattaro et al (2015) indicated that government agencies like to release posts with positive emotions to encourage citizen engagement, and that citizens prefer to interact with government Twitter accounts which deliver posts containing positive emotion. Tang et al (2019) analyzed 97,205 records from 30 provincial police micro-blogs and found that content with positive emotions was more likely to be shared, while posts containing negative emotions decreased the amount of sharing. Xu and Zhang (2018) demonstrated that tweets with positive emotions can increase the level of retweets, but content showing anger reduced those retweets.…”
Section: The Moderating Role Of Emotional Valencementioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have investigated the moderating effect of emotional valence [ 33 ]. Tang et al [ 34 ] studied the official Sina Weibo accounts of 30 provincial police departments in China and identified that emotional valence moderated the influence of content type on reposting behavior. Child-friendly content with positive emotion increased reposting the most.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have investigated the moderating effect of emotional valence [33]. Tang et al [34] studied the official Sina Weibo accounts of 30 provincial police departments in China and identified that emotional valence moderated the influence of content type on reposting behavior. Child-friendly content with positive emotion increased reposting the most.…”
Section: Research Hypotheses and Conceptual Modelmentioning
confidence: 99%